Nas causas de um sintoma social o bibliotecário atua: a mediação e uso da informação como fonte de interposição sobre o vírus HIV - OLIVEIRA, Alessandra Nunes de (Universidade Federal do Pará, 2018)
It is of importance that the professional librarian has as a mediator of information vis-à-vis the reality of social cases, with regard to concepts about the HIVAIDS. And their seriousness in-group, to bring assistance through the information, as foundations against the superstitions and misconceptions regarding HIV/AIDS. The theme is relevant to all areas therefore presents the discussions about prejudices and myths in the early 80. Above all have their goals based on addressing the social formation of own information professionals, especially the contribution of the librarian on social action for the context and the spread of the HIV virus. The methodology was a bibliographical revision about the exploratory, Almeida Júnior (1997) and Marques (2002), among others. In summary, the research used two sources of information such as the bases MEDLINE, and VHL in that sought articles published in the Decade of 80, among others found articles about the drugs that inhibit HIV among them called Zidovudine (AZT). The results show a lack of information, in which prejudice still linger in the social context. Because information workers at this point rebound the librarian, which is essential in this context, where it contributes to health professionals, to take the uncertainties, assisting on the information convalidadas to the virus carriers themselves and society.